Paediatrics: how to manage obstructive sleep apnoea syndrome - Theresa NH Leung; James WCH Cheng; Anthony KC Chan (BioExcel Publishing Ltd, 2021)
Obstructive sleep apnoea syndrome (OSAS) is defined as the intermittent reduction or cessation of airflow due to partial or complete obstruction of the upper airway during sleep. Paediatric OSAS has specific contributing factors, presenting symptoms and management strategies in various age groups. Untreated OSAS can lead to detrimental effects on neurocognitive development and cardiovascular and metabolic functions of a growing child. In the past decade, practice guidelines have been developed to guide the evaluation and management of OSAS. This article provides a narrative review on the current diagnostic and treatment options for paediatric OSAS. Alternative diagnostic tools other than the standard polysomnography are discussed. Adenotonsillectomy is considered the first-line therapy yet it is not suitable for treatment of all OSAS cases. Nocturnal non-invasive positive airway pressure ventilation is effective and could be the priority treatment for patients with complex comorbidities, residual OSAS post-adenotonsillectomy or obesity. However, intolerance and non-adherence are major challenges of positive airway pressure therapy especially in young children. There is increasing evidence for watchful waiting and other gentler alternative treatment options in mild OSAS. The role of anti-inflammatory drugs as the primary or adjunctive treatment is discussed. Other treatment options, including weight reduction, orthodontic procedures and myofunctional therapy, are indicated for selected patients. Nevertheless, the successful management of paediatric OSAS often requires a multidisciplinary team approach.